Markov Chain Analysis to Identify the Market Share Prediction of New Technology: A Case Study of Electric Vehicle Usage in Batu Pahat, Johor, Malaysia - R. Chandrashekar (Research in Management of Technology and Business, 2022)
Electric cars are thought to be an effective way to reduce greenhouse gas emissions. Electric vehicle drives have several benefits over traditional internal combustion engines, including reduced local pollution, improved energy efficiency, and less reliance on oil. However, there are considerable challenges to the quick adoption of electric vehicles, such as battery technological constraints, high purchasing prices, and a lack of charging infrastructure. The purpose of this study is to predict the future market share of electric vehicles among road users. In this research study, the quantitative method is used as the research methodology by distributing questionnaires to road users and car dealers in Batu Pahat. The data will be analyzed by Statistical Package for the Social Sciences (SPSS). The most chosen dominant factor that influcing the purchase willingness towards electric vehicle in Batu Pahat, Johor is individual environmental awareness and the least chosen is purchase cost. To attract or increase the number of purchasing electric vehicle in Batu Pahat, government may provide government financial incentives.